Adsorção dos corantes reativos azul 5G e azul turquesa QG em carvão ativado comercial - Schimmel, Daiana (2008)
The textile industries understand one of the largest of the world now in production terms and number of generated jobs. They are characterized by requesting great amounts of water, coloring and chemical products used along a complex productive chain. Besides the enormous consumption of water, those industries generate effluent composed by organic and complex salts, which ones turn pollute more when the liberation of dyes is observed no fastened, or no degraded in the conventional processes of treatment, what represents a high potential of environmental impact. Several methods of removal of dyes and of other existent chemical compositions in the effluent have been used in industrial level. One of the most employed methods is the adsorption onto carbon activated due to the versatility, efficiency and low obtaining costs. However, the project of the treatment of textile effluent for adsorption requests information regarding the removal capacity and of the kinetics. They are several factors that interfere in that process, among them they stand out the temperature and the pH, being this one what has larger effect. In this work the removal of the dyes reactive blue 5G and turquoise blue QG were investigated onto carbon activated commercial driven in system batch, once these dyes are plenty employed in the processes involving fabrics type jeans . Initially they went rehearsals to characterize the adsorbent, determination of the point of zero charge (PCZ) and of the surface area for the method BET using N2 to 77K, infrared to obtain the functional groups of the carbon, and sifting to determine the diameter of the particles. For PCZ the obtained value was of 8,10 and the surface area was of 618,7 m2/g. Kinetic tests were accomplished in pH 2 and in three different temperatures, 30, 45 and 600C. They were appraised the pseudo-first-order models and the pseudo-second-order to describe the kinetics of adsorption of the dyes, and the model of second order presented the best results. It was also certain the coefficient of diffusion of the dyes in the temperatures of 30, 45 and 600C, that presented the following values respectively: 5,38 x 10-7, 1,42 x 10-7, 2,74 x 10-7 cm2/min for the blue color 5G, and 2,54 x 10-7, 9,38 x 10-8, 1,48 x 10-6 cm2 /min for the blue turquise QG. For the influence of the pH and of the temperature in the balance of the adsorption of the dyes experiments were accomplished in system batch. The strip of investigated acidity was among pH 2 even pH 8. It was also accomplished the experiments for the obtaining of the equilibrium data in the temperatures of 30, 45 and 600C and in the best pH condition. The equilibrium data were represented by the following models of Isotherms of adsorption: Langmuir, Freudlich, Toth, Radke-Praunstiz, Sips and Redlich-Peterson. The process of adsorption had a better acting in the conditions of pH 2 and temperature of 300C, the removed amount was of 140,48 mg / g for the dye blue 5G and 148,54 mg / g for the dye turquise blue QG. The Isotherm of Sips, Tóth and Redlich-Peterson were what best represented the experimental data of equilibrium for the dye blue 5G and also for the turquoise blue QG. The thermodynamic parameters ∆H0, ∆G0 and ∆S0 were appraised and they showed that the adsorption of the colors in activated coal is an exothermic and spontaneous process due to the negative values of enthalpy and energy free from Gibbs, respectively.